Endovascular Treatment of Transplant Renal Artery Stenosis: Evaluation of Postoperative Outcomes and Risk Factors for Recurrence. (March 2019) - Roustan, François-René; Lareyre, Fabien; Bentellis, Imad; Haider, Romain; Torrino, Stéphanie; Sedat, Jacques; Albano, Laetitia; Jean-Baptiste, Elixène; Raffort, Juliette; Durand, Matthieu
Angioplasty with or without stenting has become a well-established procedure to treat transplant renal artery stenosis (TRAS). We evaluated our experience on postoperative outcomes following the intervention and identified potential predictive factors of TRAS recurrence. Consecutive patients who underwent endovascular treatment of TRAS were retrospectively reviewed. The study end points were the technical success, 30-day postoperative complications, and the estimated glomerular filtration rate (eGFR). Thirty-two patients underwent endovascular treatment for TRAS. The technical success rate was 96.6%. Complications were observed for 7 (21.9%) patients: 4 had a dissection, 2 a pseudoaneurysm, and 1 (3.1%) patient developed an acute pulmonary edema. The mean eGFR significantly increased at 7 days, 3 months, and 6 months postintervention (43.1, 44.9, and 44.3 vs 33.9 mL/min/1.73 m 2 preoperatively, P < .05). The TRAS recurrence was observed in 7 (21.9%) patients. These patients had significantly higher preoperative peak systolic velocity and systolic rise time (5 vs 4 m/s, P = .0383 and 103 vs 80 milliseconds, P = .0148, respectively). Endovascular treatment of TRAS is associated with high technical success and significant improvement in renal function. Further studies are required to confirm predictive factors of TRAS recurrence following endovascular treatment.